Thiết kế chế tạo thiết bị phát hiện và cảnh báo nguồn phóng xạ ngoài quản lý - Phan, Văn Chuân (2024)
Using the pulse shape discrimination (PSD) method to identify neutron/gamma radiation types, so that a single detector can be used to detect both neutron and gamma radiation simultaneously.